Inheritance of Traditional Chinese Medicine nursing veteran experts’ idea of humanistic care and enhancing the effect of nursing intervention on acute mastitis (传承中医护理老专家人文关怀理念 提升急性乳腺炎护理效果) - CHEN Hong (陈宏); DENG Jianhua (邓建华); LI Suqian (李苏茜); ZHOU Jie (周洁); LI Ye (李野); E Haiyan (鄂海燕); TANG Ling (郑萍); (唐玲) (中西医结合护理)
The humanistic care plays an important role in Traditional Chinese Medicine nursing. Taking acute mastitis as an example, this paper discussed the exploration, application and promotion of humanistic care concept in breast surgery, and aims to explore its role in improving the specialized nursing ability of and promoting the inheritance of Traditional Chinese Medicine nursing. (人文关怀理念在中医护理中起着重要作用。本文以急性乳腺炎为例, 论述了人文关怀理念在乳腺外科护理中的发掘、应用和推广, 旨在探讨其在提升乳腺专科护理能力和促进中医传承中的作用。)